2018
DOI: 10.1002/2017jd027874
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Radiosonde Dry Bias From Far‐Infrared Measurements on the Antarctic Plateau

Abstract: The experimental data set of downwelling radiance spectra measured at the ground in clear conditions during 2013 by a Far‐Infrared Fourier Transform Spectrometer at Dome‐C, Antarctica, presented in Rizzi et al. (2016, https://doi.org/10.1002/2016JD025341) is used to estimate the effect of solar heating of the radiosonde humidity sensor, called dry bias. The effect is quite evident comparing residuals for the austral summer and winter clear cases and can be modeled by an increase of the water vapor concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…When used in a validation exercise with FIRST measurements, which is an independent measurement data set from RHUBC-II, the derived spectroscopic parameters result in significantly improved residuals. A subsequent study by Rizzi et al (2018) confirmed, based on an analysis of a separate observational data set collected by the REFIR-PAD in Antarctica, that the new spectroscopic parameters…”
Section: Summary and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…When used in a validation exercise with FIRST measurements, which is an independent measurement data set from RHUBC-II, the derived spectroscopic parameters result in significantly improved residuals. A subsequent study by Rizzi et al (2018) confirmed, based on an analysis of a separate observational data set collected by the REFIR-PAD in Antarctica, that the new spectroscopic parameters…”
Section: Summary and Discussionmentioning
confidence: 72%
“…When used in a validation exercise with FIRST measurements, which is an independent measurement data set from RHUBC‐II, the derived spectroscopic parameters result in significantly improved residuals. A subsequent study by Rizzi et al () confirmed, based on an analysis of a separate observational data set collected by the REFIR‐PAD in Antarctica, that the new spectroscopic parameters “substantially improved the modeling of water vapor absorption in the far‐infrared.” The improved spectroscopy results in significant modifications to computed values of thermal fluxes and heating rates (Figures and ) that are likely to impact climate simulations by GCMs.…”
Section: Summary and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We use the Line-By-Line Radiative Transfer Model (LBLRTM; Clough et al, 2005) to simulate the downwelling radiance. The version used in this study is LBLRTM v12.7, with an updated line parameter database AER version 3.5 (following HITRAN 2012; Rothman et al, 2013) and a continuum code MT_CKD_3.0, which includes up-to-date C. Bellisario et al: Can downwelling FIR radiances be estimated from MIR information?…”
Section: Lblrtmmentioning
confidence: 99%
“…FIR spectral measurements of DLR proved valuable for refining the knowledge of water vapour spectroscopy (Mlawer et al, 2019) and testing the ability to model radiative transfer in the atmosphere (Mlynczak et al, 2016;Mast et al, 2017;Bellisario et al, 2019;Mlawer et al, 2019). In addition, ground-based FIR observations were successfully exploited to infer cloud properties (Maestri et al, 2014;Rizzi et al, 2016;Di Natale et al, 2017), to retrieve the thermal structure and composition of the atmosphere (Rizzi et al, 2018;Bianchini et al, 2019), as well as to conduct radiative closure studies (Delamere et al, 2010;Sussmann et al, 2016).…”
mentioning
confidence: 99%